Hermeneutika dalam Tafsir al-Mishbah: Studi Penafsiran Surat Al-Ahzab Ayat 59: STUDI PENAFSIRAN SURAH AL-AḤZĀB AYAT 59 - Himmatur Riza; Vika Rachmania Hidayah (Tanzil: Jurnal Studi Al-Quran, 2022)
Muhammad Quraish Shihab is one of the scholars and scholars of Indonesian Muslims who pursue the field of interpretation of the Qur'an. His works have contributed to the development of science in Indonesia, especially in the field of the Qur'an. Of his many works, Tafsir Al-Mishbāh: The Message, Impressions and Harmony of the Qur'an is a Masterpiece that makes his name soaring as one of the muffasir Indonesia, which is able to write the interpretation of the Qur'an 30 Juz from volumes 1 to 15. The interpretation in Q.S Al-Aḥzāb verse 59 Quraish Shihab interprets by revealing asbāb al-nuzūl verse, that before this verse came down the way of dressing women either slaves or free women is the same, therefore men with striped noses often interfere with suspecting all such women are slaves. In order to preserve the honor of the free woman, the verse goes down. According to Quraysh Shihab, in addition to differences between the scholars, Q.S Al-Aḥzāb verse 59 does not command women to wear the hijab, on the grounds that the above verses come down as they already wear the hijab, it's just that the way to wear it has not been obeyed as the verse.